Pelaksanaan Pemberian Hak Terhadap Narapidana Wanita Hamil di Lapas Kelas II A Kota Pekanbaru - Diana, Diana; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The rights between female prisoners and male prisoners are the same, only in this case because the prisoners are women, there are several rights that are given special treatment from male prisoners who differ in several ways, including because women have a nature that is not owned by male prisoners namely menstruation, pregnancy, childbirth, breastfeeding, so in this case the rights of female prisoners need special attention according to both the Law and prison officials throughout the territory of Indonesian. But the facts that occur in the field are not completely in accordance with the regulations that have been made by the government. What happened at Pekanbaru Class IIA Correctional Institution is that prisoners of pregnant women have difficulty obtaining health rights. Therefore the formulation of the problem of this thesis, namely: first, what is the implementation of the granting of rights for prisoners of pregnant women in Class IIA Lapas Pekanbaru City; Secondly, what are the barriers to granting rights for prisoners of pregnant women in Pekanbaru Class IIA Prison.This type of research can be classified in the type of empirical juridical legal research or sociological legal research. Juridical empirical research is research carried out by identifying the law and how the effectiveness of the law applies in society. This research was conducted at the Women's Penitentiary in Pekanbaru Class IIA Lapas. Data sources used, namely: primary data and secondary data. Data collection techniques in this study with Observation, Interview, and Literature Study.Conclusions that can be obtained from the results of the first study, the implementation of the granting of rights for prisoners of pregnant women in Class IIA Lapas Pekanbaru City has not been implemented properly, while based on Article 8 of Law No. 36 of 2009 concerning Health each person has the right to health as well as female prisoners pregnant, but the implementation of the exit permit was too complicated, so the implementation became ineffective. Second, the barriers to giving out permission for pregnant women prisoners in Pekanbaru Class IIA Prison namely regulations imposed in Class II A Correctional Institutions in Pekanbaru City are still in general, lack of funds and lack of infrastructure facilities so that services are inadequate, lack of professional performance of agency employees Correctional means that the rights of pregnant women prisoners are not met, the factor of the family of pregnant women prisoners who are often indifferent to the conditions of the pregnant female prisoners and the prisoners of pregnant women themselves who do not want to apply for an exit permit on the grounds that the conditions are too complicated. The author's suggestion is that it is expected that the competent government should issue laws or official regulations to fulfill women's special rights.Keywords: Rights of Prisoners-Pregnant Women-Pekanbaru